Phonon properties and photo-thermal oxidation of micromechanically exfoliated antimonene nanosheets - Fickert, Michael; Assebban, M'hamed; Canet-Ferrer, Josep; Abellán, Gonzalo (2D Materials, 2021)
Two-dimensional (2D) sheets of antimonene have attracted increasing attention due to their unique physical and chemical properties prompting potential for diverse applications. We present a facile method to prepare high-quality antimonene nanosheets (ANSs) by micromechanical exfoliation on SiO2/Si substrate. The temperature- and laser power-dependent Raman studies of exfoliated ANSs are reported and analyzed. It was found that both the out-of-plane A(1g) and the in-plane E-g modes red-shift linearly with increase in temperature, pointing towards anharmonic vibrations of the lattice. The thermal response of the ANSs on a SiO2/Si surface is also described using numerical simulation of the heat transfer to study their laser-induced oxidation mechanisms. These results offer a deeper understanding of the phonon properties and oxidation susceptibility of 2D antimonene paving the way for the development of antimonene-based technologies, such as electronic devices or photothermal cancer therapy.
CRIS-Team WoS Importer:2020-12-04